Intussusception after Colonoscopy: A Case Report and Review of Literature - Wan Amir Wan Hassan; William Teoh (Korean Society of Gastrointestinal Endoscopy, 2018)
Intussusception after colonoscopy is an unusual complication. A MEDLINE search revealed only 7 reported cases. We present a report of a 28-year-old man who developed abdominal pain several hours after routine colonoscopy and in whom computed tomography (CT) revealed colocolic intussusception. We postulate that this condition is iatrogenic and induced by suctioning of gas on withdrawal of the colonoscope. A common observation among the reported cases was abdominal pain several hours after colonoscopy and right-sided intussusception. All cases had colonoscopy reaching the right side of the colon. Treatment for adult intussusception remains controversial with regard to reduction versus resection, especially given the high association with a pathological cause and malignancy. Among the 8 reported cases, only the current case did not require surgery. A combination of benign colonoscopy, CT, and the clinical picture should provide sufficient information to initially choose a more conservative treatment approach.